My dearest duke - Vayden, Kristin (Vayden, Kristin. Cambridge brotherhood., 2022)
With the new title of Duke, something he never wanted, Rowles Haywind, in desperate need of help, reconnects with Lady Joan Morgan, and as romance blossoms between them, he discovers she is hiding a dark secret that could cause a terrible scandal should it be revealed.